The Effect of Financial Literacy and Financial Inclusion on Business Sustainability : (A Study of Women Running MSMEs Actors in Batudaa Sub-District) - Rizqika Nur Annisa Padang; Muliyani Mahmud; Nurharyati Panigoro (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze financial literacy and financial inclusion on the sustainability of businesses among women MSME actors in Batudaa District. This research method uses a quantitative approach with primary data obtained thru a questionnaire with a 1-5 Likert Scale. The population in this study consists of women MSME actors in the Batudaa district. The sample collection process used purposive sampling with a sample size of 93 respondents in this study. Data analysis was conducted using the Statistical Product and Service Solution (SPSS) method. The research results show that financial literacy and inclusion affect business sustainability. These findings indicate that understanding and the ability to manage finances, as well as easy access to formal financial products and services, are important factors in maintaining and developing a business.